The relationship between ABO and rh blood types and cow’s milk protein allergy - Ayman, Fatma Nur; Temel, Hayrettin; Nacaroğlu, Hikmet Tekin (Galenos Publishing House, 2022)
Objective: Cow’s milk protein allergy (CMPA) is the most common type of food allergy among infants. Several studies have found an association between ABO blood types and allergies such as allergic rhinitis, asthma, and atopic dermatitis, but the role of blood type differences in cases of IgE-mediated CMPA and food protein-induced-allergic proctocolitis (FPIAP) is not known yet. Methods: A total of 100 patients born in our hospital approximately 2017-2021 and followed up in our Paediatric Allergy Clinic with the diagnosis of IgE-mediated CMPA and FPIAP, and as the control group, 259 children born in our hospital who had no family history of atopy and no signs of allergic disease in the follow-up were included in the study. Blood types of healthy children, and those with IgE-mediated CMPA and FPIAP diagnosis were compared. Results: One hundred patients with CMPA were included in the study. The mean age of these patients was 10.8 months, and 49% (n=176) were male. 57% of the patients were followed up with a diagnosis of IgE-mediated CMPA and 43% with FPIAP. Familial atopy accompanied 23% (n=23) of the cases with CMPA. There was no statistically significant difference between the distribution of ABO and Rh blood types between the cases with CMPA and the control group (p>0.05). Additionally, there was no significant difference in blood type comparisons of the cases followed up with the diagnosis of IgE-mediated CMPA and FPIAP (p>0.05). Conclusion: As far as we know, this is the first study of investigating the relationship between the blood type distribution of patients with CMPA and healthy subjects. To comprehend the role of blood type in the pathogenesis of CMPA and investigate the effect of blood types on tolerance development in CMPA cases, we think prospective studies with wider groups are necessary.
The relationship between aboriginal and rh blood types and cow’s milk protein allergy
Keywords: Cow’s Milk Protein Allergy; ABO Blood Type; Rh Blood Type; Tolerance